Case report: Free autologous costal cartilage transplantation for osteochondral lesions of the talus: three cases with 2–5 years follow-up - Du, Dajiang; Chen, Jiewei; Zheng, Che; Gao, Yun; Xue, Mengxin; Zheng, Kaiwen; Xu, Peijun; Zhu, Jinyu; Zhang, Changqing (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundOsteochondral lesions of the talus (OLT) is a common and clinically challenging condition with no consensus on the optimal treatment. The prospective case series aim to evaluate the feasibility and clinical outcomes of free autologous costal cartilage transplantation (ACCT) for OLT.MethodsFrom April 2018 to October 2022, three patients who were diagnosed with OLT underwent free ACCT. Demographic characteristics, including age, gender, lesion size and location were collected at baseline. Functional and imaging outcomes were evaluated at 1 year, 2 years, and 5 years postoperatively. The primary outcomes were American Orthopedic Foot and Ankle Society (AOFAS) score and Foot and Ankle Ability Measure (FAAM) score. Secondary outcomes included Numeric Rating Scale (NRS), Tegner Activity Scale, and evaluations of images. A paired t-test was used for preoperative and postoperative comparison of the paired-design dataset.ResultsThree patients (37.33 ± 16.50 years old) were included in the study with 2–5 years follow-up. AOFAS score improved from 60 ± 11 at baseline to 96 ± 6.93 at 2 years (p < 0.01) and 94 ± 8.49 at 5 years. FAAM/ADL improved from 60.97 ± 6.58 at baseline to 98 ± 1.83 at 2 years (p < 0.01) and 97 ± 0.85 at 5 years. FAAM/Sports improved from 56.4 ± 11.95 at baseline to 88.23 ± 11.34 at 2 years (p < 0.01) and 89 ± 4.67 at 5 years. Other functional scores in patient reported outcomes also showed significant improvements. Postoperative CT and MRI showed complete defect filling and robust tissue integration after ACCT. Arthroscopic evaluations further confirmed solid integration of costal cartilage into the underlying subchondral bone with a smooth surface over the repair site.ConclusionFree ACCT is a feasible method for improving ankle function and quality of life for at least 2 years in patients with OLT. Promising long-term outcomes may be possible because of the good integration between the recipient talus and the implanted ACCT.